Dimensional Consistency Analysis in High Speed 3D Printing - Ramadhan, Doni Fajar; Sodiq, Fajar; Saputra, Hendri Maja; Putra, Mohammad Alexin (Universitas Muhammadiyah Metro, 2025)
3D printing technology has been widely applied in various industries, including manufacturing, healthcare, automotive, aerospace, and others. High 3D printing speeds, such as 1200 mm/s, offer the potential to significantly accelerate the production process. However, increasing this speed also presents challenges related to the quality and dimensional consistency of the printed parts. Therefore, understanding how each parameter interacts and affects the printing results is key to optimizing high-speed 3D printing processes. This research focuses on the dimensional accuracy of 3D printed objects. The method used involves printing 5 cube samples measuring 20mm x 20mm x20 mm with a 10 mm through all hole using Acrylonitrile Butadiene Styrene (ABS) Highspeed and Polylactic Acid (PLA) Highspeed materials at a maximum print speed of 1200 mm/s. After the printing process, the dimensions of each sample are carefully measured using a vernier caliper at three different points. PLA material tends to have a larger deviation than ABS, especially in the circle diameter parameter with a deviation percentage of 5.88%, while ABS is 5.02%. Based on the results overall the deviation of length, width, height, and hole diameter dimensions in both materials is not significant for general applications, but the deviation in hole diameter shows a higher value than other dimensions.